The Issue Price in the Initial Public Offering and the Reasons for Excluding the Company from NewConnect - Frydrych, Sylwia (Journal of Finance and Financial Law, 2022)
The purpose of the article. The subject of this article is the analysis of the change in the share price on the day of the company's debut on the NewConnect market due to the reasons for its exclusion from trading. The analysis was carried out for all companies debuting on NewConnect in 2007–2020. The results are presented depending on the share issue price. The paper hypothesized that companies whose share issue price was incorrectly estimated, which means overvalued or undervalued IPO, are more often withdrawn from the NewConnect market.Methodology. The research was carried out using the analysis of source data. In the research process, the author used, in addition to the analysis of the literature, the method of observation.Results of the research. As a result of the research, it was found that 39.84% of companies that debuted on the NewConnect market in 2007–2020 were excluded from trading. 56.28% of the withdrawn companies were forcibly excluded. On the other hand, 108 companies were withdrawn from trading voluntarily, and the prevailing premise in this group of entities was the transfer of the company to the WSE Main Market. Voluntary reasons prevail among entities withdrawn from trading, whose shares had an issue price of PLN 5 and higher. On the other hand, in the group of "penny" companies, the main reason for delisting is the safety of trading and liquidation bankruptcy. An increase in the share price on the debut day was recorded in 69.64% of entities withdrawn from NewConnect. The adopted hypothesis was positively verified. Companies whose share issue price was not properly estimated were withdrawn from the NewConnect market more often than entities whose securities price did not change on the day of their debut. The level of withdrawn companies whose IPO was overvalued and undervalued is similar. The conducted research proves that among overvalued initial public offerings, the share of voluntary reasons for withdrawal prevails, while among undervalued ones there is a higher share of forcibly excluded entities. However, the amount of the issue price according to the ranges adopted in the study does not constitute a premise for the withdrawal of companies from the NewConnect market.